2017
DOI: 10.1080/14739879.2017.1315618
|View full text |Cite
|
Sign up to set email alerts
|

The value of European exchange programs for early career family doctors

Abstract: The Hippokrates Exchange programme (HEP) is designed to give early career General Practitioners (Associates in Training (AITs)/First5s) first-hand experience into concepts of a primary healthcare system outside of their host country. The aim is to improve GP knowledge and skills, inspire professional development and promote a global approach to primary care. Although an increasing number are taking up this opportunity, their views and experiences of international exchanges are not well described. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…These findings echo those of other exchange schemes for established clinicians whether national or international. Such time is valuable; it can develop clinical practice ( Axon, 1998 ) and enhance appreciation of care and clinical practice in different contexts ( Bridgwood et al , 2017 ; Bridgwood et al , 2018 ; Jelley, 2002 ; Van Dormael et al , 2007 ; Van den Heuvel & Hood (2010) ; Zwart et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings echo those of other exchange schemes for established clinicians whether national or international. Such time is valuable; it can develop clinical practice ( Axon, 1998 ) and enhance appreciation of care and clinical practice in different contexts ( Bridgwood et al , 2017 ; Bridgwood et al , 2018 ; Jelley, 2002 ; Van Dormael et al , 2007 ; Van den Heuvel & Hood (2010) ; Zwart et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general practice and family medicine, a number of exchange programmes for established practitioners have been described: Bridgwood et al (2017) describe an evaluation of the Royal College of General Practitioner’s (RCGP) Hippokrates Exchange programme (HEP) which aims to give early career general practitioners experience of primary healthcare in another European country with the aim of developing knowledge and skills, professional development and promoting a global approach to primary care. Zwart et al (2013) describe an international exchange scheme between GP trainers and the Wessex Deanery, UK with educators from University Medical Centre (UMC), Utrecht.…”
Section: Introductionmentioning
confidence: 99%
“…They promote collaboration, shared learning and reflection on the strengths and weaknesses of different systems providing primary care. Medical electives to experience healthcare systems abroad have been a mainstay of undergraduate medical education for many years, and in recent years exchanges for postgraduate clinicians in primary care have become increasingly popular (Bridgwood et al., 2017). Given the increasing diversity and multi-culturalism of the society served by the NHS, the opportunity to experience how primary care is provided in other countries is an important addition to training (Bridgwood et al., 2017).…”
Section: Background To the Exchange Schemementioning
confidence: 99%
“…Studies have demonstrated that participants find international exchanges in primary care a positive and rewarding experience (Bridgwood et al., 2017; Bridgwood et al., 2018; Merder Coşkun et al., 2016). Qualitative evidence has captured how participants compare and evaluate differences in primary care practice and identify areas for potential improvement in their own practice during exchanges (Bridgwood et al., 2017). A large narrative review of 29 studies that considered primary care exchanges undertaken globally, considered medical students, nurses, GP trainees, GPs and visiting scholars (Bridgwood et al., 2018).…”
Section: Current Evidence Of the Benefits Of International Clinical E...mentioning
confidence: 99%
“…This preparation is helped by international partnerships. Attending a programme such as this enhances the internationalisation of your academic curricula – although the most important outcome, I believe, is in the development of soft skills (Barata and Rigon, 2015; Bridgwood et al., 2017). I strongly recommend applying to do an exchange.…”
mentioning
confidence: 99%